Acoustic and mechanical metamaterials for various applications – a brief review - Ma, Fuyin (Frontiers in Materials, 2025)
Due to the sub-wavelength structural characteristics and excellent wave regulation ability, metamaterials have important application value regulating acoustic and elastic waves. After more than 20 years of continuous development, the achievements of acoustics and elastic metamaterials have become very abundant. Especially in recent years, with the increasingly close integration with engineering application scenarios, metamaterials have shown important application value in many fields, such as aviation, aerospace, ships, rail vehicles, automobiles, home appliances, and architecture. Therefore, in order to promote the development of metamaterials in applications, we have organized three special issues, attracted the attention of many scholars, and received more than 30 submissions. To provide better guidance for the subsequent application research of metamaterials, we will briefly introduce the main breakthroughs in metamaterial applications at present, including sound absorption, sound insulation, vibration absorption, vibration isolation, noise reduction with ventilation, and acoustic detection and communication.